How Well Do We Understand the Land‐Ocean‐Atmosphere Carbon Cycle?. (6th May 2022) - Crisp, David; Dolman, Han; Tanhua, Toste; McKinley, Galen A.; Hauck, Judith; Bastos, Ana; Sitch, Stephen; Eggleston, Simon; Aich, Valentin
Abstract: Fossil fuel combustion, land use change and other human activities have increased the atmospheric carbon dioxide (CO2 ) abundance by about 50% since the beginning of the industrial age. The atmospheric CO2 growth rates would have been much larger if natural sinks in the land biosphere and ocean had not removed over half of this anthropogenic CO2 . As these CO2 emissions grew, uptake by the ocean increased in response to increases in atmospheric CO2 partial pressure (pCO2 ). On land, gross primary production also increased, but the dynamics of other key aspects of the land carbon cycle varied regionally. Over the past three decades, CO2 uptake by intact tropical humid forests declined, but these changes are offset by increased uptake across mid‐ and high‐latitudes. While there have been substantial improvements in our ability to study the carbon cycle, measurement and modeling gaps still limit our understanding of the processes driving its evolution. Continued ship‐based observations combined with expanded deployments of autonomous platforms are needed to quantify ocean‐atmosphere fluxes and interior ocean carbon storage on policy‐relevant spatial and temporal scales. There is also an urgent need for more comprehensive measurements of stocks, fluxes and atmospheric CO2 in humid tropical forests and across the Arctic and boreal regions, which are experiencing rapid change. Here, we review our understanding of the atmosphere, ocean, and land carbon cycles and their interactions, identify emerging measurement and modeling capabilities and gaps and the need for a sustainable, operational framework to ensure a scientific basis for carbon management. Plain Language Summary: Since the beginning of the industrial age in the mid‐1700s, fossil fuel combustion, land use change and other human activities have increased the atmospheric carbon dioxide (CO2 ) concentration to levels never seen before in human history. The atmospheric CO2 growth rate would have been much larger if natural sinks in the ocean and on land carbon cycle had not removed over half of the CO2 emitted by human activities. While the uptake of anthropogenic CO2 by the ocean has increased with the increasing atmospheric CO2 partial pressure, the land biosphere response has varied spatially and with time. Over the industrial age, CO2 uptake by intact forests and other natural parts of the land biosphere has roughly balanced emissions from land use change. Since the 1990s, the tropical land sink has diminished while the high latitude land sink has increased. Here, we review our understanding of the natural carbon cycle and the processes controlling its response to human activities and climate change and identify measurement and knowledge gaps. Key Points: Anthropogenic CO2 emissions would have produced larger atmospheric increases if ocean and land sinks had not removed over half of this CO2 Uptake by both ocean and land sinks increased in response to rising atmospheric CO2 levels, maintaining the airborne fraction near 45% Improved and sustained measurements and models are needed to track changes in sinks and enhance the scientific basis for carbon management